Analysis and Development of Walking Algorithm Kinematic Model for 5-Degree of Freedom Bipedal Robot - Gerald Wahyudi Setiono; Prianggada Indra Tanaya; Henricus Riyanto Hendradji (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2012)
A design of walking diagram and the calculation of a bipedal robot have been developed. The bipedal robot was designed and constructed with several kinds of servo bracket for the legs, two feet and a hip. Each of the bipedal robot leg was 5-degrees of freedom, three pitches (hip joint, knee joint and ankle joint) and two rolls (hip joint and ankle joint). The walking algorithm of this bipedal robot was based on the triangle formulation of cosine law to get the angle value at each joint. The hip height, height of the swinging leg and the step distance are derived based on linear equation. This paper discussed the kinematic model analysis and the development of the walking diagram of the bipedal robot. Kinematics equations were derived, the joint angles were simulated and coded into Arduino board to be executed to the robot.